Invisible at Work, but Visible at Home: The Indirect Effect of Ostracism on Mental Health and the Buffering-Role of Human–Animal Interactions - Lopez-Bohle, S (Emerald Publishing, 2025)
Purpose: Drawing on the integrated model of workplace ostracism and the Conservation of Resources (COR) theory, we developed and tested a multilevel model to explore the mechanisms and boundary conditions through which workplace ostracism affects employee mental health. Design/methodology/approach: In Study 1, a time-lagged field study involving 498 employees, workplace ostracism was associated with higher levels of negative affect, which in turn predicted lower levels of mental health. Findings: Study 2, a daily diary study with multiple daily measurement points, replicated the indirect effect observed in Study 1 and further demonstrated that interactions with companion animals attenuated the relationship between workplace ostracism and negative affect. Multilevel analyses revealed that end-of-day human–animal interactions moderated the indirect effect of workplace ostracism on mental health via negative affect such that the indirect effect was weaker on days when employees engaged in more frequent interactions with their companion animals. Originality/value: Together, these findings underscore the buffering role of human–animal interactions in mitigating the harmful consequences of workplace ostracism on mental health, thereby advancing theory and research on both workplace ostracism and human–animal interaction. © 2025, Emerald Publishing Limited.